2017
DOI: 10.17718/tojde.306564
|View full text |Cite
|
Sign up to set email alerts
|

Student Teachers’ Experiences of Teaching Practice at Open and Distance Learning Institution in South Africa

Abstract: This small-scale study focused on the experiences of student teachers towards teaching practice in an open and distance learning (ODL) institution in South Africa. The sample consisted of 65 fourth year students enrolled for Bachelor of Education, specializing in secondary school teaching. The mixed-method research design consisting of quantitative and qualitative approaches was used. Questionnaire and individual interview discussions were used as instruments for data collection. Descriptive statistics was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 5 publications
0
19
0
3
Order By: Relevance
“…For example, studies in South Africa by Du Plessis, (2011); Aldridge, Fraser and Ntuli, (2009) categorised the challenges into logistical and educational challenges. Because of the herculean nature of organizing teaching practice for distance programme, it was reported that some teacher training institutions have to end the teaching practice aspect of the programme (Mokoena, 2017).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…For example, studies in South Africa by Du Plessis, (2011); Aldridge, Fraser and Ntuli, (2009) categorised the challenges into logistical and educational challenges. Because of the herculean nature of organizing teaching practice for distance programme, it was reported that some teacher training institutions have to end the teaching practice aspect of the programme (Mokoena, 2017).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…[17] found that students face several challenges; among Open Access Library Journal them the fact that the period for Teaching Practice was too short, lack of instructional materials and resources in schools, poor learning environments and over-crowded classrooms, difficulties preparing notes, inadequate Teaching Practice orientation of students before actual Teaching Practice, lack of provision of field trip/excursion when necessary and other challenges that bordered on relationships with experienced teachers and personal welfare challenges of accommodation and allowances. [18] in a study of student teachers' experiences of teaching practice at open and distance learning institution in South Africa warns that the quality of teachers can deteriorate with the increasing number of students needing placement in schools. According to [19] notable challenges to teaching practice were poor placement of students in schools that did not have adequate facilities for practice, rush assessment by lecturers or supervisors due to large numbers of students they have to observe within a short time and poor management in some schools characterized by lack of timetables and mentoring staff.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concern about shortness of TP period may not be peculiar to Zambia. [18] in Benin, found that among the challenges which included the lack of teaching and learning materials, students said the TP period was too short. The same challenge was reported by [26], about Vaal University students in South Africa who reported that they were posted for TP too late in the year when most teachers had completed their syllabus and revising for examinations.…”
Section: Short Tp Periodmentioning
confidence: 99%
“…Clarke, Triggs and Nielsen (2014) further stress that a pre-service teacher mentorship programme which takes the form of teaching practice in the South African context and its supplementary practical can be regarded as an induction course that provides support to ascertain that preservice teachers are drawing out to the maximum from the available learning opportunities. Mokoena (2017) deduces that teaching practice is a period where student teachers observe teachers who are already practising in the field in order to learn about teaching skills and classroom management techniques. It is important to note that a student may not be graduated if they do not undergo teaching practice experience in South Africa.…”
Section: Introductionmentioning
confidence: 99%